Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Teknik Dasar Servis dalam Permainan Bola Voli - Rasmini, Ni Wayan (Journal of Education Action Research, 2018)
This study aims to improve service learning outcomes in volleyball games for students of Class XI K1 of SMK Negeri 3 Sukawati 2016/2017. The subjects of this study were students of Class XI Karawitan 1 in the 2016/2017 school year which amounted to 25 students. This research is a classroom action research conducted in two cycles. Each cycle consists of 2 meetings which consist of planning, action, observation, evaluation, and reflection. Data on student learning outcomes were collected through individual practice tests. The data collected was analyzed using descriptive analysis. The results of this study indicate the application of the cooperative learning model Student Team Achievement Division (STAD) can improve student learning outcomes indicated by the results of the study before the average action is obtained by students with number 7, in the first cycle increases with an average mastery of material by 67 in the less category, with a 17% increase. in cycle II it increased to 74, so the increase occurred at 17%. With enough categories. But overall, there has been a significant increase. Therefore, it is recommended that teachers in the learning process activities can use the STAD type cooperative approach to improve student learning achievement